GRP-046 Coronary Patients: Which Therapeutic Approach on Discharge from Hospital?. (12th March 2013) - Foucras, G; Denis, L; Sallerin, B; Divol, E
Abstract : Background: Coronary artery disease is one of the main causes of death in industrialised countries. The recommended treatment is 'BASI' (B for beta-blockers, A for antiplatelet agent, S for statin and I for ACE inhibitors or sartans) together with appropriate treatment of major cardiovascular risk factors (CVRFs). Purpose: To study compliance with the standard care of coronary patients, choosing to focus on hospital discharge in the context of improving professional practise. Materials and Methods: This study was conducted in two cardiology units, over 2 years. It focused on all inpatients with a positive coronary angiography. An evaluation of professional practise was conducted in 2010. Improvement actions were then taken: the results were presented to cardiologists and a booklet was written summarising good professional practise recommendations. In 2012, practise was re-evaluated through a second study. We collected and analysed information on treatment after hospitalisation, CVRFs and information in the discharge letter. Results: The study included 179 patients in 2010 and 111 in 2012. Concerning drug treatment, the recommended 'BASI' treatment was prescribed in 72% of cases in 2010 versus 70% in 2012. For non-compliant treatments (i.e. other than BASI), 17% were justified in the discharge letter (BASI not indicated or contraindicated), against 16% previously. Concerning the management of CVRF, lipid analysis was performed for 94% of patients in both groups, and recorded in the discharge letter in 82% (2010) versus 77% (2012). 30% of patients with diabetes and/or obesity consulted a dietician or diabetologist in 2010 versus 44% in 2012. Last, 68% of smokers received a nicotine substitute in 2010 and 35% in 2012. Conclusions: Our work shows that the recommendations are generally well respected. This may explain why, despite successive changes of junior doctors, practise has changed little during this study. However, further action will be required concerning management of CVRFs, which is still less satisfactory. No conflict of interest.